Spontaneous resolution of avascular necrosis of femoral heads following cure of Cushing's syndrome. (1st May 2016) - Pazderska, A; Crowther, S; Govender, P; Conlon, K C; Sherlock, M; Gibney, J
Summary: Avascular necrosis (AVN) is a rare presenting feature of endogenous hypercortisolism. If left untreated, complete collapse of the femoral head may ensue, necessitating hip replacement in up to 70% of patients. The majority of the described patients with AVN due to endogenous hypercortisolaemia required surgical intervention. A 36-year-old female, investigated for right leg pain, reported rapid weight gain, bruising and secondary amenorrhoea. She had abdominal adiposity with violaceous striae, facial plethora and hirsutism, atrophic skin, ecchymosis and proximal myopathy. Investigations confirmed cortisol excess (cortisol following low-dose 48h dexamethasone suppression test 807nmol/L; 24h urinary free cortisol 1443nmol (normal<290nmol)). Adrenocorticotrophic hormone (ACTH) was <5.0pg/mL. CT demonstrated subtle left adrenal gland hypertrophy. Hypercortisolaemia persisted after left adrenalectomy. Histology revealed primary pigmented micronodular adrenal disease. Post-operatively, right leg pain worsened and left leg pain developed, affecting mobility. MRI showed bilateral femoral head AVN. She underwent right adrenalectomy and steroid replacement was commenced. Four months after surgery, leg pain had resolved and mobility was normal. Repeat MRI showed marked improvement of radiological abnormalities in both femoral heads, consistent with spontaneous healing of AVN. We report a case of Cushing's syndrome due to primary pigmented nodular adrenocortical disease, presenting with symptomatic AVN of both hips. This was managed conservatively from an orthopaedic perspective. Following cure of hypercortisolaemia, the patient experienced excellent recovery and remains symptom free 4 years after adrenalectomy. This is the first report of a favourable outcome over long-term follow-up of a patient with bilateral AVN of the hip, which reversed with treatment of endogenous hypercortisolaemia. Learning points: AVN of femoral head can be a presenting feature of hypercortisolism, both endogenous and exogenous. Rarely, treatment of hypercortisolaemia can reverse AVN without the need for orthopaedic intervention. Primary pigmented nodular adrenal disease is a rare cause of ACTH-independent Cushing's syndrome.